PENGARUH LITERASI KEUANGAN TERHADAP KEBERLANGSUNGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN SUMBAWA - Sudiyarti, Nining; Rachman, Rosyidah; Rahayu, Dinda Fuji (Jurnal Ekonomi & Bisnis, 2024)
This study aims to determine the effect of financial literacy on the sustainability of micro, small and medium enterprises (MSMEs) in Sumbawa District. The type of this study was associative. This study used a quantitative data obtained directly from primary sources, namely MSME actors in Sumbawa District using research instruments in the form of questionnaires. The questionnaire was prepared based on research variable indicators, namely financial literacy and the sustainability of MSME businesses. All of data was studied using simple linear regression analysis techniques, partial parameter hypothesis testing (t test), and coefficient of determinant testing (R2). The results of this study showed that the financial literacy had a positive and significant effect on the sustainability of micro, small and medium enterprises in Sumbawa District. The ability of financial literacy to effect the sustainability of MSMEs in Sumbawa District was 35.6%, while the remaining 64.4% was effected by other variables outside this study model, such as the use of e-commerce, product innovation, and readiness to change.